Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/dth.15911
|View full text |Cite
|
Sign up to set email alerts
|

Gradually increasing the dosing interval of Secukinumab for moderate to severe plaque psoriasis: A single‐center, uncontrolled, prospective study in 36 weeks

Abstract: Secukinumab is a recombinant, fully human monoclonal anti-IL-17A antibody approved to treat moderate-to-severe psoriasis and psoriatic arthritis. Its effectiveness and safety have been confirmed, but a gradual increase in the secukinumab dosing interval has not been investigated. To assess the feasibility, efficacy, and safety of gradually increasing the secukinumab dosing interval; the interval duration was determined by changes in the Psoriasis Area and Severity Index scores. Patients with moderate-to-severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Meanwhile, higher clinical improvements were reported in the modified therapy study at week 24 (96%/86%/76% for PASI 75/90/100, respectively). 9 In the real-world study including 66 Chinese patients with uninterrupted treatment of 300 mg secukinumab for 52 weeks, PASI 75 rate (92.7%) at week 52 was similar with our study, while PASI 90/100 rates (63.4%, 22%, respectively) were lower. 8 The real-world evidence of these studies and our findings demonstrate the prominent effectiveness of the secukinumab in the Chinese population.…”
Section: Exploratory Analysis Of Covid-19 Vaccination and Infectionsupporting
confidence: 87%
See 3 more Smart Citations
“…Meanwhile, higher clinical improvements were reported in the modified therapy study at week 24 (96%/86%/76% for PASI 75/90/100, respectively). 9 In the real-world study including 66 Chinese patients with uninterrupted treatment of 300 mg secukinumab for 52 weeks, PASI 75 rate (92.7%) at week 52 was similar with our study, while PASI 90/100 rates (63.4%, 22%, respectively) were lower. 8 The real-world evidence of these studies and our findings demonstrate the prominent effectiveness of the secukinumab in the Chinese population.…”
Section: Exploratory Analysis Of Covid-19 Vaccination and Infectionsupporting
confidence: 87%
“…Concerning effectiveness at week 24, Jing Zhang et al 6 reported higher responses of 100%/100%/67% for PASI 75/90/100 respectively. Meanwhile, higher clinical improvements were reported in the modified therapy study at week 24 (96%/86%/76% for PASI 75/90/100, respectively) 9 . In the real‐world study including 66 Chinese patients with uninterrupted treatment of 300 mg secukinumab for 52 weeks, PASI 75 rate (92.7%) at week 52 was similar with our study, while PASI 90/100 rates (63.4%, 22%, respectively) were lower 8 .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations